Cannabis-associated psychotic-like experiences are mediated by developmental changes in the parahippocampal gyrus - Yu, Tao; Jia, Tianye; Zhu, Liping; Desrivieres, Sylvane; Macare, Christine; Bi, Yan; Bokde, Arun L. W.; Quinlan, Erin Burke; Heinz, Andreas; Ittermann, Bernd; Liu, ChuanXin; Ji, Lei; et al. (Journal of the American Academy of Child and Adolescent Psychiatry, 2020)
Objective: Cannabis consumption during adolescence has been reported as a risk factor for psychotic-like experiences (PLEs) and schizophrenia. However, brain developmental processes associated with cannabis-related PLEs are still poorly described. Method: A total of 706 adolescents from the general population who were recruited by the IMAGEN consortium had structural magnetic resonance imaging scans at both 14 and 19 years of age. We used deformation-based morphometry to map voxelwise brain changes between the two time points, using the pairwise algorithm in SPM12b. We used an a priori region-of-interest approach focusing on the hippocampus/parahippocampus to perform voxelwise linear regressions. Lifetime cannabis consumption was assessed using the European School Survey Project on Alcohol and other Drugs (ESPAD), and PLEs were assessed with the Comprehensive Assessment Psychotic-like experiences (CAPE) tool. We first tested whether hippocampus/parahippocampus development was associated with PLEs. Then we formulated and tested an a priori simple mediation model in which uncus development mediates the association between lifetime cannabis consumption and PLEs. Results: We found that PLEs were associated with reduced expansion within a specific region of the right hippocampus/parahippocampus formation, the uncus (p = .002 at the cluster level, p = .018 at the peak level). The partial simple mediation model revealed a significant total effect from lifetime cannabis consumption to PLEs (b = 0.069, 95% CI = 0.04-0.1, p = 2 x 10(-16)), as well as a small yet significant, indirect effect of right uncus development (0.004; 95% CI = 0.0004-0.01, p = .026). Conclusion: We show here that the uncus development is involved in the cerebral basis of PLEs in a population-based sample of healthy adolescents.
Gesehen am 21.07.2020